Experience of conservative treatment of genital prolapse with urogynecological pessaries - Gennady Y Yarin; Inna A Vilgelmi; Evgeny V Liuft (IP Berlin A.V., 2019)
Background. Pelvic organ prolapse is one of the most common women's diseases worldwide. Genital prolapse incidence among women over 50 is on average 41%. There are variety methods for genital prolapse treatment; they are divided into surgical and non-surgical ones. One of the conservative treatment methods is a use of pessaries. According to different studies an efficacy of pessary therapy is approximately 60%. Aim to estimate a safety and efficacy of genital prolapse conservative treatment with a cube pessary on the basis on standardized questionnaires. Outcomes and methods. In ANO "NRITO Clinic" Urology and Gynecology Center 26 women with various degree genital prolapse were treated with pessary within the period from August 2015 to March 2016. Efficacy of pessaries use, patient satisfaction with this treatment method and complications rate were estimated. Results. Urogynecological cube pessary use in a treatment of various types of genital prolapse is quite an effective method (p